2009
DOI: 10.1080/00016480902882469
|View full text |Cite
|
Sign up to set email alerts
|

Role of Kabat physical rehabilitation in Bell's palsy: a randomized trial

Abstract: Conclusion: When applied at an early stage, Kabat's rehabilitation was shown to provide a better and faster recovery rate in comparison with non-rehabilitated patients. Objective: To assess the validity of an early rehabilitative approach to Bell's palsy patients. Patients and methods: A randomized study involved 20 consecutive patients (10 males, 10 females; aged 35Á42 years) affected by Bell's palsy, classified according to the House-Brackmann (HB) grading system and grouped on the basis of undergoing or not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 11 publications
0
14
0
5
Order By: Relevance
“…The predictive role of electrophysiology improved over time due to an increased correlation with clinical findings. Nevertheless, the assessment on day 10 is more important for prognosis; degree of palsy can change within the first 10 to 14 days from onset, and early and accurate prediction is of paramount importance for the choice of different therapeutical approaches …”
Section: Discussionmentioning
confidence: 99%
“…The predictive role of electrophysiology improved over time due to an increased correlation with clinical findings. Nevertheless, the assessment on day 10 is more important for prognosis; degree of palsy can change within the first 10 to 14 days from onset, and early and accurate prediction is of paramount importance for the choice of different therapeutical approaches …”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Given the heterogeneous results in these studies, our working group was unable to achieve consensus regarding exercise physiotherapy.…”
Section: We Make No Recommendation Regarding the Use Of Exercise Physmentioning
confidence: 99%
“…[140][141][142][143] Several small studies suggested physical therapy resulted in some level of improvement in patients experiencing prolonged symptoms. 54,[140][141][142][143][144][145][146][147] Unfortunately, the therapeutic impact of physical therapy in these case reviews is impossible to separate from spontaneous recovery. 146 There was no significant difference in any measure of clinical outcome found between the different rehabilitation techniques described in the literature.…”
Section: Supporting Textmentioning
confidence: 99%